Floristic response of herbaceous flora to Intensive cropping systems: A case of Ajibode-sasa arable agroecosystem, Ibadan, Southwest Nigeria (2020)
Agriculture a most significant land use types which alter natural ecosystem dynamics. Arable farming exerts much pressure on plant biodiversity, especially when practiced intensively in urban centers. There is dearth of information on floristic changes due to intensive arable farming in urban agroecosystems in developing countries. The study therefore assessed floristic changes resulting from and intensive farming practices at Ajibode-Sasa agricultural landscape. Ajibode-Sasa agroecosystem is a complex mix of arable cropping system between latitude N07°28′, E003°53′ and longitude N07°28′, E003°54. Comparative floristic surveys were conducted in 2016 and 2020 using quadrats (1 m2) systematically laid on 18 Transects ranging from 50 – 250 m long. A total of 224 and 184 quadrats were laid in 2016 and 2020 respectively. Reduction in numbers of quadrats laid resulted from physical anthropogenic development after the 2016 survey. Species identification followed standard procedures, and quantitative occurrence data were collected for determination of species composition and computation of relative importance values (RIV) and diversity indices. Land-use changes over four years period was determined using Google earth and QGIS. Herbacous plant composition with 123 cumulative number of species in both years reduced from 98 species in 2016 to 85 species in 2020 species RIV of species ranged from 0.038 – 14.803. Tridax procumbens had the highest RIV (14.803) in 2016, while it was Acmella brachyglossa (13.248) 2020. Species richness and floral diversity was high with Shannon-Weiner Index (3.081 and 3.088) and Dominance (0.09388 and 0.08746) in 2016 and 2020 respectively. Intensive cultivation favoured introduction and spread of invasive species like Tridax procumbens and Tithonia diversifolia. Eight introduced and invasive species were newly enumerated in 2020, with a total of 38 herbaceous species no longer encountered in 2020. Concerted efforts should be made to conserve native flora on the agroecosystem through sustainable practices like crop rotation and short fallow.